Sizing inductors of an axial flux synchronous generator - D. Lahouel; D. Hedjazi; R. Abdessemed (International Journal of Applied Power Engineering (IJAPE), 2019)
This given the outcome of environmental situations in recent years, it has become necessary to use other resolutions for the energy production we need, and among these wind power sources. Since the advent of windmills to the first wind turbines, the technology of aero-motors (or wind sensors) has evolved rapidly. This article presents a study of an axial flow generator, and this mechanism is based on the energy of the wind turbine, this structure solves the problem of the distribution of the magnetic field lines in the armature coils and the inductor of the generator, observing the influence on the voltage from the linear velocity, the density of the injected current and the position along its axis; and that by the method of Finite Elements and is used the computer aided design (CAD), and more particularly the software comsol multiphysics to obtain the results that the good operation of the generator.